A study of the relationship between precipitate structure and chemistry on the mechanical properties of aluminium alloys - Warren, P; Warren, P. J. S. (1993)
﻿ The microstructural chemistry of the commercial aluminium alloy 7150, containing Al, Zn, Mg, Cu and some trace impurities, was investigated in detail. This alloy is a precipitation hardening alloy, deriving most of its strength from the fine distribution of solute rich precipitates formed during thermal processing. At peak strength this alloy suffers from the common problem of stress corrosion cracking, leading to unpredictable premature failure in the presence of a corrosive environment. Failure is mainly intergranular, thus the structure and chemistry of the grain boundary regions is of interest. A large number of previous investigations have failed to correlate any individual parameter with the stress corrosion cracking behaviour. As the analytical techniques have improved over the last three decades, more complex investigations of the microstructure and the microchemistry have been attempted, in order to more fully characterise the development of this alloy during thermal processing. This thesis presents the results of two of the highest resolution techniques available for microchemical analysis. Scanning transmission electron microscopy X-ray analysis, using a VG-HB501 dedicated scanning transmission electron microscope, enables chemical analysis with a 2nm electron probe, while atom probe analysis, using a VG-FIM100 atom probe with an additional position sensitive detector, enables single atom chemical identification with sub-nanometre spatial resolution. However, both of these techniques have their own experimental limitations which restrict the accuracy of the results obtainable. A detailed description of the many factors limiting both techniques is presented. Combining these techniques has enabled chemical analysis of all the microstructural features present in this alloy on the nanometre scale. A description of the chemical changes occurring during age hardening of this alloy is given in summary.